THE EFFECT OF ANDALIMAN FRUIT (Zanthoxylum acanthopodium DC.) ON QUALITY OF SMOKED CATFISH (Pangasius hypopthalmus) STORED AT ROOM TEMPERATURE - Mery Sukmiwati; Sumarto Sumarto; Catur Wirawan (Berkala Perikanan Terubuk, 2013)
This research was conducted in the Laboratory of Fisheries Technology,Food Microbiology and Food Chemistry, Faculty of Fisheries and Marine ScienceUniversity of Riau, Pekanbaru. The objective of this study was to evaluate theeffect of Andaliman fruit on quality of smoked catfish stored at room temperature.About 5 kg catfish weighing 700-800 g each was taken from a fish culture inKampar. The fish was hot-smoked in the smoke room for 10-16 hour. Fourgroups of smoked fish were treated with andaliman fruit liquid by snobing theliquid on the fish surface by 10%, 20%, and 30% of the fish might respectualy.The smoked fish then was oven-dried at 50-60°C for 6 hours. The smoked fishwas stored at room temperature for 45 days. Fish quality was evaluated forsensory quality, moisture, and peroxide value, at 0, 15, 30, and 45 days of storage.The result showed that the smoked fish treated with 30% andaliman liquid was thesuperior in sensory quality, and the product was still aceptable up to 45 days ofstorage. The moisture and peroxide value of the product at the end of the storagewere 18,06%, and 0,86 meq/g respectualy.Keywords: Andaliman fruits, quality, smoked catfish, room temperature